Long term renal function in Asian HIV-1 infected adults receiving tenofovir disoproxil fumarate without protease inhibitors. Issue 5 (November 2019) - Liegeon, Geoffroy; Harrison, Linda; Nechba, Anouar; Halue, Guttiga; Banchongkit, Sukit; Nilmanat, Ampaipith; Yutthakasemsunt, Naruepon; Pathipvanich, Panita; Thongpaen, Suchart; Lertkoonalak, Rittha; Althaus, Thomas; Lallemant, Marc; et al.
Highlights: The long term renal safety of TDF-based non protease inhibitors regimen was good in Asian HIV infected patients. The use of TDF was not associated with a higher risk of eGFR reduction or chronic kidney disease. The risk of eGFR reduction was greater in patients with low body weight regardless of TDF use. Summary: Objectives: The risk of kidney dysfunction on the WHO recommended first line regimens containing tenofovir disoproxil fumarate (TDF) without protease inhibitors (PI) remains unclear in Asian patients, especially those with low body weight. Methods: Using data collected in a multicenter clinical trial in Thailand and proportional hazard regression models, we compared the risk of a >25% estimated glomerular filtration rate (eGFR) reduction in HIV naïve patients initiating TDF or zidovudine (AZT) containing non-PI regimen. Results: Of 640 patients included in the analysis, 461 (72%) received a TDF-containing regimen for a median 6.7 years and 179 (28%) an AZT-containing regimen for 6.5 years. The risk of a >25% eGFR reduction was not associated with treatment (HR 1.11, 95% CI 0.84–1.47, P = 0.46). In multivariate analysis, the risk of >25% eGFR reduction form baseline was associated with body weight at baseline (HR 2.12, 95% CI 1.48–3.02 for <48 kg patients and HR 1.64, 95% CI 1.20–2.25 for 48–59.9 kg patients, compared to those with >60 kg, P < 0.001) and hypertension (HR 4.03, 95% CI 2.0–8.0, P < 0.001). The effect of baseline weight on >25% eGFR reduction did not significantly vary with treatment ( P = 0.27). Conclusions: The risk of eGFR reduction was not higher on TDF- versus AZT-based non-PI regimens. Although the risk of eGFR reduction was greater for patients of lower body weight, this risk was not significantly increased by TDF.